El manuscrito m971 de la biblioteca de Catalunya (misa de Barcelona) (Barcelona Biblioteca de Catalunya, 1989)
The Barcelona Mass is a polyphonic mass written around 1360. Together with the Messe de Nostre Dame by Guillaume de Machaut and those of Toulouse, Tournai and the Sorbonne, it is one of the earliest preserved complete polyphonic musical settings of the Ordinary of the Mass. It is believed to belong to the repertoire of the Papal court at Avignon and is also linked to the chapel of King Martin I of Aragon.It is preserved in a single manuscript kept in the Biblioteca de Catalunya in Barcelona (ms. 971), where it was found in 1925 by the musicologist Higinio Anglés.It consists of the usual five parts, the Kyrie, Gloria, Credo, Sanctus and Agnus Dei. The Agnus Dei is written in four voices, while the other movements have three. The five parts are not written according to a unifying structural pattern and may have been written by different anonymous composers. The Gloria and Credo have also been independently preserved as standalone pieces in other sources. Unlike other mass cycles of the period, the Barcelona Mass contains neither a motetus over Ite, missa est nor a setting of the Benedictus, and its movements are not based on plain chant.